Pengaruh Model Pembelajaran Model Problem Based Learning Dalam Meningkatkan Kemampuan Berpikir Spasial Di SMAN 13 Samarinda - Ningrum, Mei Vita Romadon; Perkasa, Galih (geoedusains: Jurnal Pendidikan Geografi, 2024)
Problem based learning is learning model that is considered capable of improving spatial thinking skills is the problem-based learning. This model is a learning model that is based on constructivism and accommodates student involvement in learning and engaging in contextual problem solving. This research was conducted with the aim of knowing the effect of the problem-based learning model on the spatial thinking skills of SMA Negeri 13 Samarinda class students in geography subject. The sample in this study consisted of 2 classes, namely class X IPS 1 as the experimental class using the problem based learning and class X IPS 2 as the control class using the discovery learning model. The data collection method was carried out using a test in the form of a pre-test and post-test. Based on the results of the analysis using the anova test, it can be seen that the sig values ​​(p-values) for the experimental and control classes were 0.000 and 0.001 respectively, which were smaller than the significance level of 0.05. It was concluded that problem based learning affects the ability to think spatially.